The Relationship Between Budget Participation and Managerial Performance: The Role of Moderator Variables Interaction - Johny Manaroinsong; Tinneke E.M. Sumual; Hisky R. Kawulur (AIBPM Publisher, 2018)
The purpose of this research is to find out the effect of budget participation on managerial performance which is moderated by leadership style, obedience pressure and budget goal commitment. This research utilises the design of the influence among moderating variables. Data collection techniques utilised questionnaires which were circulated to leaders and civil servants who participated in budgeting for the 19 agencies /authorities and offices in Manado City totaling 173 respondents. Data were analyzed by Moderated Regression Analysis test. The findings of the study exhibited that the effect of budget participation on managerial performance becomes stronger through leadership styles, obedience pressure and budget goal commitment. Keywords: Budget participation, managerial performance, leadership style, obedience pressure, budget goal commitment